On the existence of ordered phases of encapsulated diamondoids into carbon nanotubes - Legoas, S. B.; Dos Santos, R. P B [UNESP]; Troche, K. S.; Coluci, V. R.; Galvao, Douglas S. (Springer Nature, 2012)
We have investigated some diamondoids encapsulation into single walled carbon nanotubes (with diameters ranging from1.0 up to 2.2 nm) using fully atomistic molecular dynamics simulations. Diamondoids are the smallest hydrogen-terminated nanosized diamond-like molecules. Diamondois have been investigated for a large class of applications, ranging from oil industry to pharmaceuticals. Molecular ordered phases were observed for the encapsulation of adamantane, diamantane, and dihydroxy diamantanes. Chiral ordered phases, such as; double, triple, 4- and 5-stranded helices were also observed for those diamondoids. Our results also indicate that the modification of diamondoids through chemical functionalization with hydroxyl groups can lead to an enhancement of the molecular packing inside the carbon nanotubes in comparison to non-functionalized molecules. For larger diamondoids (such as, adamantane tetramers), we have not observed long-range ordering, but only a tendency of incomplete helical structural formation. © 2012 Materials Research Society.
Keywords: Adamantanes; Atomistic molecular dynamics simulations; Chemical functionalization; Diamantanes; Diamond-like; Diamondoids; Hydroxyl groups; Long-range ordering; Molecular packings; Oil industries; Ordered phasis; Structural formation; Tetramers; Chemical modification; Graphene; Hydrogen; Molecules; Oligomers; Stereochemistry; Carbon nanotubes